1988
DOI: 10.1073/pnas.85.18.6885
|View full text |Cite
|
Sign up to set email alerts
|

Model-building study of the combining sites of two antibodies to alpha (1----6)dextran.

Abstract: Models of the Fv portion (containing the variable regions of the heavy and light chains) of two monoclonal anti-a(1-÷6)dextran antibodies, W3129 and 19.1.2, were constructed from amino acid sequences and the known three-dimensional structures of the Fv portions of McPC603 and J539. The modeled combining site of W3129 has a protrusion on one side, formed by the long complementaritydetermining region 1 of the light chain and the long complementarity-determining region 3 of the heavy chain, and has a cavity accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…This may be explained, in part, by the Ab structures that bind them. In several instances, peptide-and CHO-reactive mAbs have been shown to possess groove-like binding sites (28)(29)(30)(31). Work by Vargas-Madrazo et al (32) suggests that the majority of anti-CHO Abs use a limited subset of V genes, indicating that this class of Abs uses a restricted structural repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained, in part, by the Ab structures that bind them. In several instances, peptide-and CHO-reactive mAbs have been shown to possess groove-like binding sites (28)(29)(30)(31). Work by Vargas-Madrazo et al (32) suggests that the majority of anti-CHO Abs use a limited subset of V genes, indicating that this class of Abs uses a restricted structural repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that small epitopes generally include the nonreducing terminal residue, whereas larger epitopes are located along the length of the polysaccharide chain (17). It was further suggested that small epitopes bind to cavity-type antigen-binding-site topologies, whereas larger internal epitopes are recognized by groove-type topologies (18). Although few bacterial oligosaccharideantibody crystal structures have been reported to date (19)(20)(21), these early estimates of epitope size and nature, and their relationship to binding-site topology, are largely concordant with current structural data.…”
Section: Discussionmentioning
confidence: 99%
“…Cavity-like and groove-type sites for anti-carbohydrate antibodies, including antibodies to LPS OAg from Shigella flexneri, Vibrio cholerae, and Brucella abortus, were supported by immunochemical, computer modeling, and x-ray crystallographic studies. (41)(42)(43)(44)(45)(46)(47)(48)(49)(50) These showed a maximum of five sugar residues accommodated by cavity-type sites and six to eight sugar residues accommodated by groove-type sites. In the current study, FB11 may have a cavity-type site and the other three anti-Ft OAg MAbs likely have groove-type sites.…”
Section: Biacore Analysis Confirms Higher Avidity Of End-binding Mabmentioning
confidence: 99%